2006
DOI: 10.1073/pnas.0510380103
|View full text |Cite
|
Sign up to set email alerts
|

Caspase recruitment domain protein 6 is a microtubule-interacting protein that positively modulates NF-κB activation

Abstract: Proteins containing a caspase recruitment domain (CARD) play pivotal roles in signal transduction leading to apoptosis and NF-B activation and inflammation. Here we identify and characterize human and mouse CARD protein 6 (CARD6), CARD-containing proteins of unique structure. CARD6 associates with microtubules and interacts with receptor-interacting protein (RIP)-like interacting caspase-like apoptosis regulatory protein kinase (RICK), a CARD-containing member of the RIP family of protein kinases. These kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
55
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 27 publications
0
55
0
Order By: Relevance
“…From the exome sequencing data, we further identified three mutated genes (CARD6, NSD1, and NLRP13) that are associated with NF-κB activation. CARD6 (caspase activation and recruitment domain family, member 6) negatively regulates NF-κB activation by NOD1 (nucleotide-binding oligomerization domain containing 1) receptor in human embryonic kidney-derived HEK293T cells (20,21) whereas the effect is reversed in Huh7 cells of hepatocarcinoma origin (22), thus indicating that the role of CARD6 in NF-κB activation may be cell-type specific.…”
Section: Transcriptome Sequencing and Pathway Analysis For Resistancementioning
confidence: 99%
“…From the exome sequencing data, we further identified three mutated genes (CARD6, NSD1, and NLRP13) that are associated with NF-κB activation. CARD6 (caspase activation and recruitment domain family, member 6) negatively regulates NF-κB activation by NOD1 (nucleotide-binding oligomerization domain containing 1) receptor in human embryonic kidney-derived HEK293T cells (20,21) whereas the effect is reversed in Huh7 cells of hepatocarcinoma origin (22), thus indicating that the role of CARD6 in NF-κB activation may be cell-type specific.…”
Section: Transcriptome Sequencing and Pathway Analysis For Resistancementioning
confidence: 99%
“…Although much progress has been made in assigning precise roles to most CARD-containing proteins, the functions of the 1,037-amino-acid (aa) human and 1,175-aa mouse CARD6 proteins are still unknown. CARD6 has a unique structure in that it contains the CARD at the N terminus, a glutamic acid-rich region following the CARD, and a proline-rich region at the C terminus (7). CARD6 also harbors a ϳ350-aa region with similarity to upregulated gene 4 (URG4), a protein that is induced in response to hepatitis Bx antigen overexpression and exerts a positive effect on proliferation (36).…”
mentioning
confidence: 99%
“…Our initial characterization of human CARD6 showed that this protein associates with microtubules in a CARD-and proline-rich region-dependent manner (7). CARD6 also interacts with RIP2 (also known as RICK or CARDIAK), a CARD-containing member of the RIP family of protein kinases (25).…”
mentioning
confidence: 99%
See 2 more Smart Citations